A defensin with highly potent antipathogenic activities from the seeds of purple pole bean. Issue 2 (10th November 2009) - Lin, Peng; Wong, Jack Ho; Ng, Tzi Bun
Abstract : A 5443 Da peptide with sequence homology to defensins was purified from purple pole beans ( Phaseolus vulgaris cv. 'Extra-long Purple Pole bean'). This peptide was isolated by adsorption on an affinity chromatographic medium Affi-Gel Blue gel and ion-exchange chromatographic media SP-Sepharose (sulfopropyl-Sepharose) and Mono S and by gel filtration on Superdex peptide. The peptide inhibited mycelial growth in Mycosphaerella arachidicola, Helminthosporium maydis, Fusarium oxysporum, Verticillium dahliae, Rhizoctonia solani, Candida albicans and Setosphaeria turcica with an IC50 of 0.8, 0.9, 2.3, 3.2, 4.3, 4.8 and 9.8 μM respectively. Its antifungal potency was higher than that of the plant defensin coccinin (IC50 >50 μM). It induced membrane permeabilization in C. albicans as evidenced by SYTOX Green uptake, but did not affect erythrocyte membrane permeability. It inhibited growth in M. arachidicola by inducing chitin accumulation at hyphal tips as was shown by Congo Red staining. The antifungal activity was pH stable and thermostable. The peptide inhibited the proliferation of hepatoma (HepG2), breast cancer (MCF7), colon cancer (HT29) and cervical cancer (SiHa) cells but not that of human embryonic liver (WRL68) cells. Its anti-HepG2 activity (IC50 =4.1±0.8 μM, n =3) was higher than that of another plant defensin, gymnin (IC50 >50 μM). Its anti-MCF7 activity (IC50 =8.3±0.3 μM, n =3) was similar to that of other plant defensins. It reduced the activity of HIV-1 reverse transcriptase with an IC50 of 0.5±0.1 μM, n =3, much more potently than other plant defensins (IC50 >40 μM). There is the possibility of using the purple pole bean defensin for producing antifungal drugs and/or transgenic plants with fungal resistance.